2022
DOI: 10.55519/jamc-02-9215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Yogurt Versus Probiotics for the Management of Acute Diarrhoea

Abstract: Background: The advantages of probiotic administration for acute diarrhoea are mainly shorter duration of symptoms as well as reduced number of stools per day while use of traditional yogurt has similar results. So, this study was conducted to compare the efficacy of yogurt with probiotic in children with acute gastroenteritis. Methods: This randomized controlled trial was conducted at department of Pediatrics, Children Hospital, Pakistan Institute of Medical Sciences, Islamabad over 1 year. A total of nine hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Thirteen studies reported the frequency of a sedentary lifestyle in patients. An Indian study 51 reported a frequency of only 5%, whereas a study in Pakistan 24 indicated physical inactivity in 86% of the study patients.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thirteen studies reported the frequency of a sedentary lifestyle in patients. An Indian study 51 reported a frequency of only 5%, whereas a study in Pakistan 24 indicated physical inactivity in 86% of the study patients.…”
Section: Resultsmentioning
confidence: 84%
“…Nepalese patients who were smokers were observed in 58.6% 22 to 80.8% 14 of the study population. Similarly, smoking was prevalent in 14.3% 23 to 64.7% 24 of Pakistani patients and in up to 77.4% 25 of Bangladeshi patients. However, 12 studies also mentioned the use of smokeless tobacco—with a frequency ranging from 0.3% 26 to 60.6% 27 —as a risk factor in patients.…”
Section: Resultsmentioning
confidence: 96%
“…Non‐significant results were stated after 24 h of intervention between the control group administered with simple yogurt and the experimental group treated with the probiotic lactobacillus rhamnosus . The mean frequency of diarrhea reduced in both groups during first 24 h of intervention (Anjum et al, 2022). The incidence of diarrhea was found to reduce with the administration of Lactobacillus casei strain Shirota (LcS) contained within fermented milk (Mai et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…However, in the case of women's predominance reported by Zhu et al, our study was quite the opposite and it showed more male predominance compared to females. Studies by Abusharifah et al [ 19 ], Anjum et al [ 20 ], and Dehghani et al [ 21 ] also reported male predominance with 81%, 76.19%, and 74.5%, respectively. However, this fact needs to be followed up with larger sample sizes and preferably multicenter studies to find out if there is any gender predominance.…”
Section: Discussionmentioning
confidence: 97%